Reflecting and Integrating the Contextual Influences of Ambiguities and Institutional Power in Organisational Research Design: A Case of Myanmar. (June 2019) - Win, Sandar; Kofinas, Alexander K.
ABSTRACT: Our understanding of how an organisation operates is elucidated by the host country's political system. Myanmar has remained abstruse to researchers for many decades, as do most emerging markets prior to their transition from a centrally planned economy to a market economy such as China. We establish how the problematising and contextualisation of the methodologies adopted during longitudinal fieldwork in Myanmar (2008 to 2016) has influenced our research focus and question. By reflecting on our experience of conducting organisational research in a highly institutionalised environment, we have identified limitations in the prevalent research methodologies used by the extant literature. Such methodologies tend to be incompatible with the Asian context. This process of problematisation required us to remain flexible and adaptive during the process of the generation of the research questions. We adopted a context-informed theory-building process and reflect on the interplay between interviewer, interviewees, and local institutional contexts. An important insight from this process was the need to nullify the asymmetry of power between the interviewer and interviewees to obtain honest responses rather than superficial data that aimed to satisfy and please the interviewer/institutional context. 摘要: 我们对于组织运作的理解是由东道国政治制度来解释的。缅甸几十年来对于研究者而言一直是难于理解的，这同像中国这样的大多数新兴经济体在实现从计划经济转型为市场经济之前的情形一样。我们阐明，在缅甸从事追踪田野研究（2006-2016）期间所采取的问题解决和方法论的情境化，怎样影响了我们的研究焦点和问题。通过反省我们在高度制度化环境下从事组织研究的经验，我们发现，已有文献中采用的主流研究方法存在不足，这些方法论与亚洲情境不契合。解决问题的过程要求我们在产生研究问题的过程中保持灵活性和适应性。我们采用了一个情境知会式理论建立过程，反映访问者、被访者和当地情境的互动。从这个过程中获得的重要洞见在于，要消除访问者和被访者之间的权力不平衡才可以获得诚实的回答，而非获得旨在满足访问者/制度情境的肤浅数据。 АННОТАЦИЯ: Наше представление о том, как работают организации, сводится к политической системе в конкретной стране. В течение многих десятилетий, Мьянма оставалась труднодоступной для исследователей, как и большинство развивающихся рынков до перехода от централизованной плановой экономики к рыночной экономике, как, например, Китай. Мы показываем, каким образом проблематизация и контекстуализация методов исследования, которые применялись в ходе продолжительной полевой работы в Мьянме (2008–2016 гг), повлияли на постановку вопроса и направление в наших исследованиях. На основании нашего опыта проведения организационных исследований в стране с сильными институтами, мы обнаружили ряд ограничений в распространенных методах исследований, которые используются в существующей литературе. Такие методы, как правило, несовместимы с азиатским контекстом. Этот процесс проблематизации потребовал, чтобы мы оставались гибкими и адаптивными в процессе постановки вопросов исследования. Мы использовали контекстуальный процесс построения теории, а также задумались о взаимодействии интервьюера, интервьюируемых и местных институциональных контекстов. Важным выводом из этого процесса стала необходимость нейтрализовать асимметрию неравенства между интервьюером и интервьюируемыми для того, чтобы получить честные ответы, а не поверхностные сведения, которые имеют своей целью понравиться и удовлетворить интервьюера / институциональный контекст. RESUMEN: Nuestro entendimiento de cómo una organización funciona es esclarecido por el sistema político del país anfitrión. Myanmar ha permanecido recóndito para los investigadores durante muchas décadas, al igual que la mayoría de los mercados emergentes antes de su transición de una economía de planificación centralizada a una economía de mercado como China. Establecemos cómo la problematización y contextualización de las metodologías adoptadas durante un trabajo de campo longitudinal en Myanmar (2008 a 2016) ha influido en nuestro enfoque y pregunta de investigación. Al reflexionar sobre nuestra experiencia llevando a cabo investigaciones organizacionales en un entorno altamente institucionalizado, hemos identificado limitaciones en las metodologías de investigación prevalecientes utilizadas por la literatura existente. Tales metodologías tienden a ser incompatibles con el contexto asiático. Este proceso de problematización requirió que nos mantuviéramos flexibles y adaptativos durante el proceso de generación de las preguntas de investigación. Adoptamos un proceso de construcción de teorías basado en el contexto y reflexionamos sobre la interacción entre quién entrevista, los entrevistados y los contextos institucionales locales. Una reflexión importante de este proceso fue la necesidad de anular la asimetría de poder entre el entrevistador y los entrevistados para obtener respuestas honestas en lugar de datos superficiales que pretendían satisfacer y complacer al entrevistador/ contexto institucional.